Waste Analysis Using Lean Service Approach In PackageDelivery Activities From The Warehouse To The Main Branch (Case Study: PT XYZ Station Center) - Widiastuti, Nova; Gunawan, Suwardi; Pawitra, Theresia Amelia (Jurnal Teknik Industri (JATRI), 2025)
The delivery of goods from warehouses to branch offices plays a crucial role in ensuring operational efficiency and customer satisfaction. However, inefficiencies in the delivery process often result in waste, such as excessive waiting times, unnecessary movements, and high operational costs. This study aims to analyze waste in the goods delivery process using the Lean Service approach and provide recommendations for improvement. Data collection methods include direct observation, interviews with logistics personnel, and process mapping to identify non-value-added activities. The results indicate that applying Lean Service principles, such as streamlining workflows, reducing unnecessary handling, and optimizing resource utilization, can significantly enhance delivery efficiency. Implementing these strategies helps minimize delays, reduce costs, and improve service quality. The findings of this study are expected to contribute to the development of more efficient supply chain management strategies and serve as a reference for companies looking to optimize their logistics operations.